Si doping-induced phase control, formation of p-type and n-type GaAs nanowires. (January 2022) - Kang, Yubin; Tang, Jilong; Azad, Fahad; Zhu, Xiaotian; Chen, Xue; Chu, Xueying; Wang, Dengkui; Fang, Xuan; Fang, Dan; Lin, Fengyuan; Li, Kexue; Wang, Xiaohua; et al.
Abstract: We realized the control on the crystal structure of GaAs nanowires (NWs) by silicon (Si) doping and V/III ratio. This viewpoint has been clearly evidenced by Raman spectrum combined with high-resolution transmission electron microscopy (HRTEM). Undoped GaAs NWs generally show a mixture of zinc blende (ZB) and wurtzite (WZ) phases; the addition of Si dopant and high V/III ratio are beneficial for the nucleation of ZB structure. Field effect transistor (FET) devices were fabricated to show that Si-doped GaAs NWs exhibit p-type conductivity in the low V/III ratio of 25.8 and n-type conductivity in the high V/III ratio of 51.6. These results provide a clear route for achieving GaAs NWs phase control and different conductivity types, which is an essential step towards the fabrication of nanoscale devices. Highlights: Phase control, formation of p-type and n-type GaAs NWs were designed and fabricated by Si doping and V/III ratio using MBE. The doping-induced phase control from WZ/ZB mixed phase to the pseudo-pure phase ZB structure in the GaAs NWs were clearly revealed. Si-doped GaAs NWs exhibit p-type and n-type conductivity with different V/III ratios were determined by FET.